The Impact of Mutations in Wolframin on Psychiatric Disorders - Munshani, Saira; Ibrahim, Eiman Y.; Domenicano, Ilaria; Ehrlich, Barbara E. (Frontiers in Pediatrics, 2021)
Wolfram Syndrome is a rare autosomal recessive disease characterized by early-onset diabetes mellitus, neurodegeneration, and psychological disorders. Mutations in the gene WFS1, coding for the protein wolframin, are associated with psychiatric diseases including bipolar disorder and schizophrenia. This report aims to connect WFS1 mutations to their impact on protein expression and structure, which ultimately translates to altered cell function and behavioral alterations of an individual. Methods: Published data were used to compile WFS1 mutations associated with psychiatric symptoms, both in homozygous patients and heterozygous carriers of WFS1 mutations. These mutations were evaluated in silico using SNAP2, PolyPhen-2, and PROVEAN to predict the effects of sequence variants. Statistical analysis was performed to assess the correlation between the locations of the mutations and the damage prediction scores. Results: Several mutations, clustering in the center and C-terminus of the WFS1 polypeptide, such as A559T and R558C, are found in individuals with psychiatric diseases and appear particularly impactful on protein structure. Our analysis showed that mutations in all regions of wolframin were associated with schizophrenia whereas only cytoplasmic and ER luminal mutations were reported in patients with manic episodes and bipolar disorders. According to Poly-Phen-2 predictions, 82.4% of the ER lumen mutations and 85.7% of the membrane mutations are damaging. Conclusion: We propose mood disorders in Wolfram Syndrome and heterozygous carriers of WFS1 mutations are the consequence of specific mutations in WFS1 that alter the structure of wolframin, resulting in intracellular calcium dysregulations and impaired cell signaling, Understanding the effect of WFS1 mutations on psychiatric diseases is integral to designing clinically targeted treatments for both diseases, which both need more specialized treatments.